Processing of Rice Straw (Oryza sativa) into Activated Carbon and Its Formulation in Facial Cleansing Soap Products - Regina Elianda Tampubolon; Suci Wulandari; Jhon Patar Sinurat; Reh Malem Br Karo (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Rice straw is an abundant agricultural by-product commonly used as livestock feed or burned as waste. It contains cellulose, hemicellulose, lignin, and silica, which can be processed into activated carbon capable of adsorbing impurities and excess oil from the skin. To date, the utilization of rice straw has been limited mainly to compost fertilizer and planting media. Meanwhile, facial cleansing soaps made from natural extracts, eco-friendly ingredients, and affordable materials are increasingly popular. The objective of this study was to produce activated carbon from rice straw and apply it in the formulation of a facial cleansing soap product.This research employed an experimental laboratory approach with a quantitative descriptive method to determine the effectiveness of rice straw–based activated carbon in facial soap formulations. The procedure began with the carbonization of rice straw powder, followed by characterization of the activated carbon through moisture content analysis, ash content test, and FT-IR functional group analysis. The liquid soap was formulated into three variations and evaluated for its quality through organoleptic observation, pH measurement, cleansing ability test, and oil adsorption test.The results showed that activated carbon derived from rice straw had a moisture content of 8.92%, ash content of 7.68%, and exhibited functional groups such as –OH, aliphatic C–H, aromatic C=C, aldehyde C=O, and alcohol C–O based on FT-IR analysis. The facial soap formulations containing rice straw–based activated carbon demonstrated safe pH values—F1 = 5.46, F2 = 6.04, and F3 = 6.8—and exhibited enhanced cleansing and oil-adsorbing properties, with the highest oil adsorption value reaching 86%. These findings indicate that activated carbon from rice straw can be effectively applied in the formulation of facial cleansing soap that is safe and beneficial for skin health.